Identification of a Wee1-like kinase gene essential for procyclic Trypanosoma brucei survival. - Natalia Y Boynak (Public Library of Science (PLoS), 2013)
Regulation of eukaryotic cell cycle progression requires sequential activation and inactivation of cyclin-dependent kinases (CDKs). Activation of the cyclin B-cdc2 kinase complex is a pivotal step in mitotic initiation and the tyrosine kinase Wee1 is a key regulator of cell cycle sequence during G2/M transition and inhibits mitotic entry by phosphorylating the inhibitory tyrosine 15 on the cdc2 M-phase-inducing kinase. Wee1 degradation is essential for the exit from the G2 phase. In trypanosomatids, little is known about the genes that regulate cyclin B-cdc2 complexes at the G2/M transition of their cell cycle. Although canonical tyrosine kinases are absent in the genome of trypanosomatids, phosphorylation on protein tyrosine residues has been reported in Trypanosoma brucei. Here, we characterized a Wee1-like protein kinase gene from T. brucei. Expression of TbWee1 in a Schizosaccharomyces pombe strain null for Wee1 inhibited cell division and caused cell elongation. This demonstrates the lengthening of G2, which provided cells with extra time to grow before dividing. The Wee1-like protein kinase was expressed in the procyclic and bloodstream proliferative slender forms of T. brucei and the role of Wee1 in cell cycle progression was analyzed by generating RNA interference cell lines. In the procyclic form of T. brucei, the knock-down of TbWee1 expression by RNAi led to inhibition of parasite growth. Abnormal phenotypes showing an increase in the percentage of cells with 1N0K, 0N1K and 2N1K were observed in these RNAi cell lines. Using parasites with a synchronized cell cycle, we demonstrated that TbWee1 is linked to the G2/M phase. We also showed that TbWee1 is an essential gene necessary for proper cell cycle progression and parasite growth in T. brucei. Our results provide evidence for the existence of a functional Wee1 in T. brucei with a potential role in cell division at G2/M.